Association between certain foods and risk of acute myocardial infarction in women. Issue 6727 (24th March 1990) - Gramenzi, A; Gentile, A; Fasoli, M; Negri, E; Parazzini, F; La Vecchia, C
Abstract : STUDY OBJECTIVE--To examine the relation between selected foods and acute myocardial infarction in women. DESIGN--Case-control study conducted over five years. SETTING--30 Hospitals with coronary care units in northern Italy. SUBJECTS--287 Women who had had an acute myocardial infarction (median age 49, range 22-69 years) and 649 controls with acute disorders unrelated to ischaemic heart disease (median age 50, range 21-69 years) admitted to hospital during 1983-9. MAIN OUTCOME MEASURES--Frequency of consumption of various foods and odds ratios of risks associated with these foods. RESULTS--The risk of acute myocardial infarction was directly associated with frequency of consumption of meat (odds ratio 1.5 for upper v lower thirds of consumption), ham and salami (1.4), butter (2.3), total fat added to food (1.6), and coffee (2.8). Significant inverse relations were observed for fish (0.6), carrots (0.4), green vegetables (0.6), and fresh fruit (0.4). The risk was below one for moderate alcohol consumption (0.7) and above one for heavier intake (1.2). Allowance for major non-dietary covariates, including years of education, smoking, hyperlipidaemia, diabetes, hypertension, and body mass index, did not appreciably alter the estimates of risk for most of the foods; for coffee, however, the odds ratio fell to 1.8 on account of its high correlation with smoking. CONCLUSIONS--The frequency of consumption of a few simple foods may provide useful indicators of the risk of myocardial infarction. Furthermore, specific foods such as fish, alcohol, or vegetables and fruits may have an independent protective role in the risk of cardiovascular diseases.